`Turning on' to glutathione: a rhodamine-based fluorescent chemodosimeter with nanomolar sensitivity - Badekar, Pooja S.; Deo, Harshada S.; Varma, Mokshada E.; Kulkarni, Prasad P.; Maibam, Ashakiran; Krishnamurty, Sailaja; Kumbhar, Anupa A. (ChemistrySelect, 2024)
A new colorimetric and fluorescence turn-on chemodosimeter for selective detection of GSH over Cys and Hcy with 34-fold enhancement in emission intensity is reported. Probe 1 exhibited ultra-sensitivity toward GSH with 0.125 nM detection limit and successfully displayed GSH detection in MCF-7 live cells. The mechanism of sensing is established by density functional theoretical calculations.
Keywords: Chemodosimeter; Fluorescence turn-on; GSH; MCF-7 cells; Rhodamine